Knowledge, attitude, and practice assessment in diabetic foot ulcer grading: a prospective cohort observational study - Manimozhi, K.; Lokeshvaran, D.; Theesmi Bershani, P.; Jayaseelan, J.; Abinish, D. G. (International Journal Of Community Medicine And Public Health, 2024)
Background: Diabetes is a group of disorders marked by chronic high blood sugar due to issues with insulin. It includes type 1, type 2, genetic and drug-induced types, and gestational diabetes. A serious complication of diabetes is diabetic foot ulcers (DFUs), caused by peripheral neuropathy, vascular problems, and infections, which can lead to severe outcomes like amputations. Methods: A prospective cohort observational study was conducted over six months at a tertiary care teaching hospital involving 163 diabetic patients with foot ulcers, aged 20 to 80. The study assessed knowledge, attitude, and practices (KAP) regarding DFUs using a translated KAP questionnaire. Ulcer grades were classified using the Wagner system. Data were collected on socio-demographic factors, disease-related factors, and practices related to foot care. Results: This study found most of the participants were under the age group of 41-50, with a higher prevalence of females, and predominantly had type 2 diabetes. Common co-morbidities included hypertension, eye issues, and cardiovascular disease. Ulcer grading showed that most patients had Wagner grade 2 ulcers. Many participants lacked awareness about diabetes-related foot risks. Although most were open to lifestyle changes, many had gaps in foot care, with few following recommended practices. Conclusions: The study highlights the importance of better patient education and counselling to manage diabetic foot ulcers effectively. Although participants had a positive attitude towards foot care, there were significant gaps in their knowledge and practices. Healthcare providers, including pharmacists, need to improve education and communication to address these issues and help prevent severe complications.